Iterative Algorithm for the Effects of Atmospheric Refraction on the Equatorial Coordinates of a Star Valid for any Zenith Distance - Sharaf, Mohammed (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
In the present paper an efficient algorithm will be established for the effects of atmospheric refraction on the equatorial coordinates of a star valid for any zenith distance The algorithm uses two new iterative schemes, the first is linear iterative scheme for the equatorial coordinates due to atmospheric refraction. The second is the quadratic Newton iterative scheme for obtaining the true zenith distance from Bennent formulae for the atmospheric refraction. Description of the algorithm was also given together with numerical applications.